The Role of Irregular Words in Linguistic Function in Sheikh Hamlawi's "Shadh al-'Urf fi Fan al-Sarf": A Descriptive and Analytical Study (The International Journal for Scientific Research, 2026)
This research aims to explore the role of irregular words in language development. The researcher addressed the theoretical framework related to irregularity and its role in language development, drawing on the book "Shadd al-'Urf fi Fan al-Sarf" by Sheikh al-Hamlawi. The descriptive-analytical method was employed, and the research sample consisted of middle and high school students. Data was collected through questionnaires designed specifically for this research. The researcher concluded that irregular words are not errors, but rather represent an expansion of analytical understanding of morphological patterns and the reasons behind their deviation from standard usage. They also constitute morphological diversity, allowing for a reinterpretation of texts within the context of Arabic usage. Furthermore, they provide morphological material that enables the original concepts to be circulated and used, rather than being considered rigid errors.
Keywords: Role of Irregularity; Development; Measurement; Discourse; Contribution